2001
DOI: 10.1016/s0009-9236(01)26448-0
|View full text |Cite
|
Sign up to set email alerts
|

Losartan attenuates symptomatic and hormonal responses to hypoglycemia in humans

Abstract: Ibuprofen pharmacokinetics showed a large interindividual variation in premature infants during treatment for patent ductus arteriosus, and significant changes may occur between day 3 and day 5 after birth in those infants with a closing ductus. These findings may have implications for the treatment schedule with ibuprofen in patients with patent ductus arteriosus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
55
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(64 citation statements)
references
References 25 publications
7
55
2
Order By: Relevance
“…As expected, our study demonstrated a lower Cmax than those reported with intravenous ibuprofen administration 30. The interesting finding in our analysis is that the area under the curve (AUC) 0→24 was higher in the oral regimen when compared with the intravenous route, as demonstrated in figure 1.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…As expected, our study demonstrated a lower Cmax than those reported with intravenous ibuprofen administration 30. The interesting finding in our analysis is that the area under the curve (AUC) 0→24 was higher in the oral regimen when compared with the intravenous route, as demonstrated in figure 1.…”
Section: Discussionsupporting
confidence: 80%
“…Two examined intravenous administration29 30 and only one31 reported ibuprofen pharmacokinetics following oral administration (table 4). …”
Section: Discussionmentioning
confidence: 99%
“…The population PK models (see Supplementary File 1) were compared with respect to birth weight, gestational age (GA), and postnatal age (PNA) of the cohort, ibuprofen-dosing regimen, route of administration, and studied ibuprofen enantiomers [12, 22, 23, 30, 31]. …”
Section: Methodsmentioning
confidence: 99%
“…(R)-ibuprofen is a relatively weak inhibitor of COX-2 [21]. The metabolism of ibuprofen has been shown to mature during early life [12, 22], with CYP2C8 mainly responsible for the metabolism of (S)-ibuprofen, and CYP2C9 for (R)-ibuprofen. The mean half-lives for (S)- and (R)-ibuprofen in preterm infants of about 34 h and 8 h at birth, respectively [23], followed by a very rapid increase of (R)-ibuprofen elimination during the first days of life.…”
Section: Introductionmentioning
confidence: 99%
“…In an attempt to support their conclusion, they compare ibuprofen area under the curve (AUC) 0→24 generated by their study with data generated by two studies of intravenous ibuprofen 2 3. This explanation of oral ibuprofen superiority is problematic from several perspectives.…”
mentioning
confidence: 99%